2018
DOI: 10.4992/jjpsy.88.16064
|View full text |Cite
|
Sign up to set email alerts
|

Does a prevention focus evoke a persistent style when performing a creative task?

Abstract: Literature in the field of regulatory focus theory argues that individuals who are promotion-focused in creativity-related tasks are more successful than those who are prevention-focused. However, recent studies have shown that prevention-focused individuals are persistent when solving tasks, potentially leading to improved task performance. This study, which considered two kinds of regulatory focus (chronic/situational), investigated the hypothesis that prevention-focused individuals employ a persistent style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Therefore, people those who experience regulatory fit engage more strongly in their goal pursuit, which leads to better performance (e.g., Förster et al, 1998; Markman et al, 2005; Shah et al, 1998, and others). The effect of regulatory fit has been confirmed in many different fields, such as value (Avnet & Higgins, 2006), creativity (Nagaya & Nakayachi, 2017), persuasion (Cesario et al, 2004), and task performance (Förster et al, 1998; Shah et al, 1998).…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, people those who experience regulatory fit engage more strongly in their goal pursuit, which leads to better performance (e.g., Förster et al, 1998; Markman et al, 2005; Shah et al, 1998, and others). The effect of regulatory fit has been confirmed in many different fields, such as value (Avnet & Higgins, 2006), creativity (Nagaya & Nakayachi, 2017), persuasion (Cesario et al, 2004), and task performance (Förster et al, 1998; Shah et al, 1998).…”
Section: Introductionmentioning
confidence: 90%
“…These persuasion-related framing effects are called goal-framing effects (Levin, Schneider, & Gaeth, 1998). Studies on goal-framing effects have generally shown that negative framing is more persuasive than positive framing in various domains, such as disease control, infectiousdisease prevention (Block & Keller, 1995), and disaster prevention (Nagaya & Nakayachi, 2019). These framing effect studies suggest that people attach greater weight to negative consequences and monetary losses.…”
Section: Loss Aversion In the Framing Effectmentioning
confidence: 99%
“…In the context of goal‐framing effects, the impact on attitude change and the formation of behavioral intentions may also depend on the magnitude of the loss. In previous studies, negative‐framing messages are effective for life‐threatening issues, such as fatal disease prevention and disaster prevention (Krishnamurthy, Carter, & Blair, 2001; Nagaya & Nakayachi, 2019). However, the effectiveness of negative framing has not yet been confirmed for low‐threat illnesses, such as skin cancer.…”
Section: The Explanatory Model Of Loss Aversion and Predicted Boundar...mentioning
confidence: 99%
“…Nine studies analyzed the association between individuals' RAT performance and certain abilities and traits, including blink counts (Chermahini and Hommel, 2010;Ueda et al, 2016), humor , work performance (Op den Kamp et al, 2018), perception (Zmigrod and Zmigrod, 2016), mental health (LeBoutillier and Barry, 2018), adventurism (Shen et al, 2018), and self-evaluation (Harkins, 2006;Nagaya and Nakayachi, 2017). These studies revealed the correlation between creativity and other variables, which indirectly shows the impact of creativity on individuals' performance.…”
Section: Predictor or Criterionmentioning
confidence: 99%